Early versus Late Feeding after Cesarean Delivery: A Randomized Controlled Trial - Saad, Antonio F.; Saoud, Fawzi; Diken, Zaid M.; Hegde, Shruti; Kuhlmann, Maggie J.; Wen, Tony S.; Hankins, Gary D.; Saade, George R.; Costantine, Maged M. (American Journal of Perinatology, 2016)
Objective This study aims to evaluate whether early feeding after cesarean delivery (CD) shortens the time to pass flatus and bowel movement.Methods Women at term undergoing CD were randomly assigned to start oral intake either within 6 hours (early feeding) or after 12 hours (late feeding) from surgery completion. Women with preeclampsia, or requiring emergent CD, additional bowel surgery, or the use of general anesthesia were excluded. Our primary outcome was time of passing first flatus following surgery completion. Secondary outcomes included time of first bowel sounds, time of first bowel movement, nausea/vomiting, and length of maternal hospital stay (clinicaltrials.gov identifier NCT02396485).Results A total of 177 women were randomized to early (n  =  85) or late feeding (n  =  82). There was no loss to follow-up, and outcomes were available for all patients. There were no differences in baseline characteristics between the two groups. Early feeding resulted in shorter time to pass flatus (median [interquartile range], 715 [485–1,208] minutes vs. 1,300 [820–1,760] minutes; p < 0.001) and to have bowel sounds (232 [168–537.8] minutes vs. 554.5 [202–706] minutes; p = 0.001). Time to pass bowel movement was shorter in the early-feeding group, but did not reach significance. The groups did not differ in length of stay or in rates of nausea, vomiting, or ileus.Conclusion In women undergoing CD, early oral intake is well tolerated and results in earlier return of bowel function.
Keywords: cesarean; feeding; pregnancy; postpartum